Lei Geral de Proteção de Dados: a indispensabilidade de uma regulamentação específica para esporte - Soares, Fernanda Cristina Santos (2023)
The protection of personal data is a fundamental right, expressly recognized as such in the Federal Constitution of 1988. The General Data Protection Law (“LGPD”) is a milestone in Brazilian legislation: for the first time the country has a specific law for the personal data protection. LGPD places the subject of personal data at the center of the legislation, recognizing a series of rights to be exercised over their personal data before the agents responsible for their treatment. For each right recognized by the Law, there is a duty of the processing agent. To agents who do not comply with the duties established by law, administrative sanctions may be applied. Among the foreseen sanctions is the partial or total prohibition of the exercise of activities related to data processing. Sport, a social fact and fundamental right, especially that recognized in performance sports and training sports, is organized in sports entities. Such entities enjoy autonomy regarding their organization and functioning. In the exercise of their activities, sports entities carry out massive processing of personal data, of different types of holders, including sensitive personal data, those that enjoy special protection from the LGPD given the seriousness of the impact of any incident with such personal data to the subject. In case of non-compliance with the LGPD, sports entities can be sanctioned in a way to make the continuity of their activities unfeasible, which could mean a threat to the enjoyment of the fundamental right to sport. The impact of sport on society and the specificity of its activities demonstrates the indispensability of specific personal data protection regulations along the lines of Article 50 of the LGPD